2010
DOI: 10.12702/1984-7033.v10n02a08
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity in yellow passion fruit (Passiflora edulis Sims) based on RAPD

Abstract: -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…The number of polymorphic bands observed was 94 (84%), while the number of monomorphic bands observed was 18 (16%). This percentage of polymorphic bands is according to the data available in the literature for characterizations carried out with species of passion fruits through RAPD markers, as with the wild species P. alata (Bellon et al, 2009) and P. nitida , as well as for the cultivated species P. edulis Cerqueira-Silva et al, 2010). Genetic diversity in P. trintae based on molecular markers…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…The number of polymorphic bands observed was 94 (84%), while the number of monomorphic bands observed was 18 (16%). This percentage of polymorphic bands is according to the data available in the literature for characterizations carried out with species of passion fruits through RAPD markers, as with the wild species P. alata (Bellon et al, 2009) and P. nitida , as well as for the cultivated species P. edulis Cerqueira-Silva et al, 2010). Genetic diversity in P. trintae based on molecular markers…”
Section: Resultsmentioning
confidence: 90%
“…In this sense, access to molecular polymorphism at the DNA level optimizes the generation of knowledge useful for conserving the diversity of Passiflora spp, for example, the studies carried out using restriction enzymes of chloroplast DNA sites (Sánchez et al, 1999), isoenzymes (Segura et al, 2003), amplified fragment length polymorphism (Segura et al, 2002) and random amplified polymorphic DNA (RAPD) (Fajardo et al, 1998;Viana et al, 2003;Junqueira et al, 2007;Bellon et al, 2007Bellon et al, , 2009Cerqueira-Silva et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The use of molecular markers is fundamentally important for enhancing the amount of information generated and for reducing the time required to obtain results (Ferreira and Rangel 2011). In this context, we note a considerable increase in research devoted to obtaining estimates of genetic variability using molecular markers in both commercial (Ortiz et al 2012;Costa et al 2012;Cerqueira-Silva et al 2010a;Bellon et al 2007;Viana et al 2003) and wild passion fruit species (Cerqueira-silva et al 2010b(Cerqueira-silva et al , c, 2012aJunqueira et al 2007). These studies have identified low variability among commercial accessions of P. edulis and generally wide variability among wild accessions of passion fruit, reinforcing the potential for the use of these materials as a resource in breeding programs.…”
Section: Introductionmentioning
confidence: 99%
“…In molecular diversity characterizations, RAPD markers (random amplified poly-morphic DNA) (Williams et al, 1990) have been widely used in Passiflora species, such as P. alata (Bellon et al, 2005), P. edulis Sims (Bellon et al, 2007;Cerqueira-Silva et al, 2010a), P. trintae (Cerqueira-Silva et al, 2010b), and Passiflora spp (Viana et al, 2010). We quantified, by RAPD markers and complement of the Dice index, the dissimilarity of wild genotypes of 'sleep' passion fruit, originating from the region of Vitória da Conquista, Bahia, Brazil, and belonging to the CAGT-Passiflora/UESB 'Planalto de Conquista'.…”
Section: Introductionmentioning
confidence: 99%